Formation of suspension structure in the process of grinding in bead mills - Hrininh-Hera, Kateryna; Gubenia, Oleksii; Telychkun, Yuliia (My University, 2020)
It has been investigated the rheological properties of the suspension of farmaceutical and cosmetics preparates during grinding at an experimental laboratory bead mill of periodic action. The rheological characteristics have been investigated on a rotary viscometer Reotest 2. as a result of the research, the flow curve of the suspension during grinding has been constructed and it has been found that within the investigated range the product does not change the character of flow regardless of measurement time and temperature. Analysis of the curve of the suspension during grinding revealed features which explain formation of the structure. The dependence of the effective viscosity on the shear rate during grinding of the suspension is polynomial and confirms the non Newtonian character of the product and is defined as a linear plastic body. The investigated finished product has 6.5 time’s higher viscosity in relation to pure castor oil, which is explained by the high dry matter content (40 %) and the increase in the newly formed area. The viscosity of the suspension varies depending on the temperature: cooled to 20 °C, the finished product has a viscosity of 22.5% higher than immediately after the grinding process with a temperature of 34 °C
Keywords: grinding; suspension; shear stress; shear rate; effective viscosity; надтонке подрібнення; суспензія; напруження зсуву; швидкість зсуву; ефективна в'язкість; кафедра машин і апаратів харчових та фармацевтичних виробництв